You can't screw this up : why eating takeout, enjoying dessert, and taking the stress out of dieting leads to weight loss that lasts - Bornstein, Adam (William Morrow, an imprint of HarperCollinsPublishers, 2023)
A trusted nutrition consultant, whose clients include LeBron James, Cindy Crawford, Arnold Schwarzenegger, and Lindsey Vonn, uses proven life-changing methods to paint a clear picture of why stepping away from dieting methods can end the vicious cycle of weight gain.